Pengaruh Kepercayaan dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pengguna Jasa Pengiriman Paket Pada PT. JNE Express Cabang Jember dengan Kepuasan Sebagai Variabel Intervening - Frizky Yuniarta; Ika Barokah S.; Gusti Ayu Wulandari (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
This study aims to knowing the influence of trust and service quality to customer loyalty users delivery service package in PT. JNE Express Branch Jember with satisfacton as intervening variables. This study is explanatory research. Population is all customer of PT. JNE Express whoever sent the package. The sampling method for this study was used with purposive sampling technique and it got 104 respondents as samples. Data analysis method is Path Analysis. The result of study showed that path analysis determined the influence of trust toward satisfaction showed positive relation. It indicates that the better trust could increase customer satisfaction. Path analysis determined the influence of trust toward customer loyalty showed positive relation. It indicates that the better trust could increase customer loyalty. Path analysis determined the influence of service quality toward satisfaction showed positive relation. It indicates that the better service quality could increase customer satisfaction. Path analysis determined the influence of service quality toward customer loyalty showed positive relation. It indicates that the better service quality could increase customer loyalty. Path analysis determined the influence of customer satisfaction toward customer loyalty showed positive relation. It indicates that the better customer satisfaction could increase customer loyalty. Keywords: Trust, Customer Satisfaction, Service Quality, Loyalty.